Actuation of an elastic membrane by the use of an electrorheological valve. Issue 1 (25th January 2021) - Schomberg, Thomas; Gerland, Florian; Wünsch, Olaf; Rütten, Markus
Abstract: The dynamic response of a fluidic actuator is investigated on the basis of numerical simulations. With this actuator a membrane is excited to oscillate by means of an electrorheological valve. For this purpose the solid and fluid domains are coupled. Furthermore, the constitutive equation of the fluid is coupled to the electric field. The dynamic response is discussed on the example of a variable stiffness of the membrane. Actuators of this type offer the potential to delay the transition of a boundary layer.